2016
DOI: 10.1002/chem.201504066
|View full text |Cite
|
Sign up to set email alerts
|

A Water‐Soluble Copper–Polypyridine Complex as a Homogeneous Catalyst for both Photo‐Induced and Electrocatalytic O2 Evolution

Abstract: The water-soluble polypyridine copper complex [Cu(F3TPA)(ClO4)2] [1; F3TPA=tris(2-fluoro-6-pyridylmethyl)amine] catalyzes water oxidation in a pH 8.5 borate buffer at a relatively low overpotential of 610 mV. Assisted by photosensitizer and an electron acceptor, 1 also exhibits activity as a homogeneous catalyst for photo-induced O2 evolution with a maximum turnover frequency (TOF) of (1.58 ± 0.03) × 10(-1) s(-1) and a maximum turnover number (TON) of 11.61 ± 0.23. In comparison, the reference [Cu(TPA)(ClO4)2]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
51
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 56 publications
2
51
1
Order By: Relevance
“…Despite not fully elucidating these factors, there have been numerous advances in molecular catalyst design for water oxidation. [11][12][13] Their superior biomimetic reactivity [14] with oxygen, and the unique covalent metal-oxo bonding in Cu 2 (m-O) 2 core are expected to be advantage for oxygen evolution. [10] Owing to inexpensive and easily accessible to different oxidation state,c opper-based molecular water oxidation catalysts have been documented with the focus on mono-and bi-nuclear copper complexes.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Despite not fully elucidating these factors, there have been numerous advances in molecular catalyst design for water oxidation. [11][12][13] Their superior biomimetic reactivity [14] with oxygen, and the unique covalent metal-oxo bonding in Cu 2 (m-O) 2 core are expected to be advantage for oxygen evolution. [10] Owing to inexpensive and easily accessible to different oxidation state,c opper-based molecular water oxidation catalysts have been documented with the focus on mono-and bi-nuclear copper complexes.…”
mentioning
confidence: 99%
“…Recrystallization of [(L Gly -Cu) 4 ] from acetonitrile/water solution gave rise to dark green blockshaped crystals.T he X-ray crystal structure revealed that [(L Gly -Cu) 4 ]( L Gly :3 -methoxy-salicylidene-glycine) featured au nique tetrameric cubane-like structure.A ss hown in Figure 1, each Cu atom is coordinated with one Na tom and five Oatoms.T aking Cu1 as arepresentative,the N1, O2, and O3 atoms from one horizontal ligand and the O2' atom from another vertical ligand are sited in the equatorial plane,while the O2'' and O1' atoms are arranged in an apical fashion. Thet urnover frequency (TOF) is determined to be 267 s À1 for [(L Gly -Cu) 4 ]at1.70 Vand 105 s À1 for [(L Glu -Cu) 4 ]at 1.56 V. Theexceptional catalytic efficiency, higher than those of mono-or binuclear ones (0.4-100 s À1 ) [11][12][13] enable us to believe that the Cu 4 O 4 cubane core is promising for the catalytic oxygen evolution. Indeed, the assynthesized cubane complexes ([(L Gly -Cu) 4 ]and [(L Glu -Cu) 4 ]) exhibit superior oxygen evolution ability in aqueous solution (pH 12).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Transition metal complexes are widely used to catalyze the organic reactions . Chelation reaction of polymers with metal ions provides useful properties depending on the structure of metal‐chelate, including high temperature and flame resistant, low leaching the metal ion to the reaction mixture, and recyclability of the metal loaded polymers .…”
Section: Introductionmentioning
confidence: 99%